Механізм формування крупномасштабної ''плямовидної'' структури забруднення підстеляючої поверхні потужним газо-аерозольним викидом у нижній частині атмосфери - Волощук, В.М.; Скриник, О.Я.; Грицюк, Ю.Я. (Видавничий дім "Академперіодика" НАН України, 2007)
Basing on the numerical solution of the diffusion problem, we show the consistency of the hypothesis that a possible forming mechanism of a large scale spot-like pollution structure of the underlying surface under intense aerosol injections into the atmospheric boundary layer is a periodic change (diurnal variation) of the turbulent state of the environment.